Many systems, one strategy: Acquiring ordinals in Dutch and English. Issue 1 (12th October 2020) - Meyer, Caitlin; Barbiers, Sjef; Weerman, Fred
Abstract : This study compares ordinal acquisition in Dutch and English, and shows that both groups of learners acquire ordinals via a rule, rather than lexically. Our evidence comes from a Give-X type comprehension task (cf. Wynn 1992, Meyer et al. 2018, under review ) which we administered to 70 Dutch L1 learners (2;08–4;11) and 35 learners of American English (3;3–5;3). The data not only offer a replication of the core findings in Meyer et al. (2018 ), showing that Dutch-speaking children acquire irregular forms (such as derde 'third') after they acquire regular synthetic forms (such as vierde 'fourth'), but also show that (i) children acquire irregular forms after analytic forms (e.g., boot zes 'boat six'), and (ii) the rule-based pattern that holds for Dutch also holds for English. We argue that children use the ordinal form to acquire its meaning, which implies that ordinals are acquired in a different way than cardinal numerals (which follow a slow, sequential pattern), and also what is typically described for derivation (which initially tends to follow a lexical pattern, i.e., one in which complex forms are stored as wholes before children learn they can be formed productively by means of a rule).